Joint trajectories of cognition and gait speed in Mexican American and European American older adults: The San Antonio longitudinal study of aging. (17th April 2020) - Gonzales, Mitzi M.; Wang, Chen‐Pin; Quiben, Myla; MacCarthy, Daniel; Seshadri, Sudha; Jacob, Mini; Hazuda, Helen
Abstract: Objectives: Cognitive decline and gait speed slowing are independent predictors of disability and mortality. While both factors increase in prevalence with advancing age, little is known about their combined patterns of change. The study goal was to identify joint trajectories of cognition and gait speed within an aging bi‐ethnic cohort of Mexican Americans and European Americans. Methods/Design: Participants included 182 Mexican Americans and 188 European Americans, ages 65 to 74, who were followed over a mean of 9.5 years. Cognition was assessed with the mini‐mental state examination and gait speed was examined with a timed 10‐ft walk. Joint trajectory classes of cognition and gait speed were identified with latent growth mixture modeling. Odd‐ratios assessed predictors for trajectory classes. Results: Three latent trajectory classes were identified: (a) relatively stable cognition and gait (termed stable cognition and gait class, 65.4%); (b) deteriorating cognition and gait (termed cognitive and physical vulnerability class, 22.2%); (c) stable cognition and deteriorating gait (termed physical vulnerability class, 12.4%). The odds of classification in the cognitive and physical vulnerability class vs stable cognition and gait class was associated with Mexican American ethnicity (OR = 3.771, P = .016), age (OR = 1.186, P = .017), income (OR = 0.828, P = .029), education (OR = 0.703, P < .001), and diabetes (OR = 4.547, P = .010). The odds of classification in the physical vulnerability class was associated with female sex (OR = 6.481, P = .004) and body mass index (OR = 1.118, P = .025). Conclusions: The trajectories of cognition and gait speed were generally parallel, suggesting the two domains may act synergistically to shape important health outcomes. Socioeconomic disparities and Mexican American ethnicity independently conferred risk for accelerated decline.